2004
DOI: 10.1103/physrevlett.92.205701
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Melting of Ice in Contact withSiO2

Abstract: The physical behavior of condensed matter can be drastically altered in the presence of interfaces. Using a high-energy x-ray transmission-reflection scheme, we have studied ice-SiO2 model interfaces. We observed the formation of a quasiliquid layer below the bulk melting temperature and determined its thickness and density as a function of temperature. The quasiliquid layer has stronger correlations than water and a large density close to rho(HDA)=1.17 g/cm(3) of high-density amorphous ice suggesting a struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
136
1
12

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(160 citation statements)
references
References 26 publications
11
136
1
12
Order By: Relevance
“…A surface prefreezing effect seems most unlikely, since it would be contrary to the premelting effect of ice observed at a macroscopic ice/silica interface. 13 The satellite peak might originate from some structural transition in the nonfreezing contact layer near the pore walls or, even more speculative, from a transition in the core of the pore liquid at a temperature above its freezing point. Further work is needed to elucidate the nature of this small transition.…”
Section: Comparison Of Dsc and Nmr Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A surface prefreezing effect seems most unlikely, since it would be contrary to the premelting effect of ice observed at a macroscopic ice/silica interface. 13 The satellite peak might originate from some structural transition in the nonfreezing contact layer near the pore walls or, even more speculative, from a transition in the core of the pore liquid at a temperature above its freezing point. Further work is needed to elucidate the nature of this small transition.…”
Section: Comparison Of Dsc and Nmr Resultsmentioning
confidence: 99%
“…The classical theories of wetting phenomena 12 predict that in this case a thin liquid-like layer will intervene between the solid and the wall at and somewhat below the solid/liquid coexistence temperature. For ice against a macroscopically flat silica surface it was found 13 that interfacial premelting starts at a temperature 15 K below T 0 and that the thickness of the quasi-liquid layer strongly increases as T 0 is approached. Theoretical studies have indicated, however, that for curved substrates all wetting transitions are suppressed and, for cylinders and spheres, the prewetting transition is smeared by finite-size effects.…”
Section: Introductionmentioning
confidence: 99%
“…544 In other words, interfacial melting occurs at the ice-amorphous SiO 2 contact, just the opposite of the phenomenon mentioned for crystalline silica interfaces. The thickness of the interfacial layer within which the chemical and physical…”
Section: Water On Amorphous Hydroxylated Silicasmentioning
confidence: 99%
“…542 Before entering into the details of the main contributions, it is worth mentioning the major experimental data that sheds light on the influence of the hard matter (silica) on the soft one, even at short length scales (1 nm or less): Shen et al 543 reported that water at the interface with Q(0001) organizes in an ice-like structure in a certain pH range (Figure 37a). At the opposite, Engemann et al 544 evidenced that amorphous silica induces a liquid-like layer at the silica-ice interface ( Figure 37b). However, experiments do not -or not yet-give information on the local H-bond breaking/making between silanols and water.…”
Section: Adsorption Of Water On Silica Surfacesmentioning
confidence: 99%
“…This work, supported by the NSF Chemistry Division, has been carried out with many collaborators and has been heavily influenced by a number of experimentalists including S.-H. Chen [44,50,77,82], L. Liu [39,40], F. Mallamace [85,86], O. Mishima [13,87,88], J. Teixeira [89][90][91], M.-C. Bellissent [92][93][94][95], and H. Reichert [96].…”
Section: Acknowledgmentsmentioning
confidence: 99%